2010
DOI: 10.1099/jmm.0.015032-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identity of aminoglycoside-resistance genes in Escherichia coli isolates from human and animal sources

Abstract: A bacterial collection (n=249) obtained in Hong Kong from 2002 to 2004 was used to investigate the molecular epidemiology of aminoglycoside resistance among Escherichia coli isolates from humans and food-producing animals. Of these, 89 isolates were gentamicin-sensitive (human n=60, animal n=29) and 160 isolates were gentamicin-resistant (human n=107, animal n=53). Overall, 84.1% (90/107) and 75.5% (40/53) of the gentamicin-resistant isolates from human and animal sources, respectively, were found to possess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 26 publications
3
44
0
Order By: Relevance
“…The witness for this claim is the frequent studies in which the presence of resistance, high-level aminoglycoside resistance, and other antibiotic resistance genes have been indicated in human, animals and food resources (25)(26)(27)(28). Overall, there are scarce reports on aminoglycoside resistance genes in Salmonella species (13).…”
Section: Discussionmentioning
confidence: 99%
“…The witness for this claim is the frequent studies in which the presence of resistance, high-level aminoglycoside resistance, and other antibiotic resistance genes have been indicated in human, animals and food resources (25)(26)(27)(28). Overall, there are scarce reports on aminoglycoside resistance genes in Salmonella species (13).…”
Section: Discussionmentioning
confidence: 99%
“…The genes corresponding to the phenotypic resistance to important classes of antibiotics were identified. Resistance to streptomycin in all isolates was common (66.8%) and in the vast majority was associated with the presence of strA/strB genes, which were described as a part of Tn5993 transposon (10,11). Some of these strains were intI-positive.…”
Section: Discussionmentioning
confidence: 99%
“…In many previous studies, it was shown that the use of antibiotics is a risk factor for the selection of multi-resistant E. coli in both humans and animals (7,10,11,17). The results of the research examining a set of isolates derived from sows in farms with different levels of antibiotics consumption indicate that the vast majority of E. coli strains are multi-resistant and have a similar or the same resistance pattern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations